Voices of Harmony: Exploring Peace and National Unity in Nigerian Arabic Literature - Yusuf, Tajudeen (Universitas Darussalam Gontor, 2025)
Since the old age, Literature as a mirror of society and its development often explores themes of morality, compassion, unity and peaceful coexistence in human society. Through poems and proses, literature can convey ethical principles that promote and educate peaceful coexistence, respect for others, and harmonious social relationships. Using descriptive method, this paper attempt to explore the contributions of Arabic Literature of Nigerian Authorship in promoting national integration, harmony and peaceful co-existence among Nigerian citizen with diverse ethnics and constituencies; literary texts (Poetry) were selected in the works of three literary icons. This study examines how Nigerian-authored Arabic literature fosters unity, harmony, and peaceful coexistence in Nigeria’s diverse socio-political landscape. It highlights the contributions of prominent Arabic literary figures, who are Muslims and products of rigorous Arabic and Islamic scholarship. Through their works, they promote ideals of social cohesion and mutual understanding. Their literary contributions serve as a bridge for fostering peace and unity in the nation.. The results of the study reveals that many literary scholars have contributed, through their literary productions, to the promotion of national integration, harmony and peaceful co-existence among the people who speak a multitude of languages and have array of cultural diversities and practices.